2022
DOI: 10.3390/ijgi11020114
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Scaling Urban Transformative Resilience through Utilizing Volunteered Geographic Information

Abstract: Resilience in the urban context can be described as a continuum of absorptive, adaptive, and transformative capacities. The need to move toward a sustainable future and bounce forward after any disruption has led recent urban resilience initiatives to engage with the concept of transformative resilience when and where conventional and top-down resilience initiatives are less likely to deliver effective strategies, plans, and implementable actions. Transformative resilience pathways emphasize the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 120 publications
0
12
0
Order By: Relevance
“…From this perspective, we expect a growth rate of research focused on governance patterns based on citizen science research and active involvement of key local actors in decision-making for place-based resilience planning. Recent works also refer to reflexive urban governance and people’s empowerment from the viewpoint of transformative and anticipatory resilience, using knowledge, social innovation and digital technology as facilitators (Moghadas et al, 2022 ; Zeng et al, 2022 ).…”
Section: Discussion and Conclusion Normative Relevance And Future Res...mentioning
confidence: 99%
“…From this perspective, we expect a growth rate of research focused on governance patterns based on citizen science research and active involvement of key local actors in decision-making for place-based resilience planning. Recent works also refer to reflexive urban governance and people’s empowerment from the viewpoint of transformative and anticipatory resilience, using knowledge, social innovation and digital technology as facilitators (Moghadas et al, 2022 ; Zeng et al, 2022 ).…”
Section: Discussion and Conclusion Normative Relevance And Future Res...mentioning
confidence: 99%
“…The most recent perspective, evolutionary/transformative resilience, or the non-equilibrium model of resilience [11], acknowledges the variety of ways in which cities can evolve and views the urban environment as a venue for constant change, adaptation, and transformation [12]. Overall, while the engineering perspective views resilience as recovery and the ecological perspective views resilience as compatibility or adaptability capacity, the evolutionary/transformative perspective considers resilience to be a more positive transformation [13] and a bounceforth process [14,15]. Planning responses supporting different interpretations of resilience can vary significantly in their value propositions and approaches to implementation [16].…”
Section: Literature Review 21 Planning For Urban Resiliencementioning
confidence: 99%
“…In forming the resilience content in spatial plans, bottom-up and participatory approaches can make greater contributions. Planners in China are therefore advised to make clever use of community knowledge and crowdsourcing of volunteered geographic information [15] and to combine pluralistic governance approaches when refining spatial resilience initiatives.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…In the study of Mikhailenko et al (2021), they aimed to address the use of information technologies in the implementation of inclusive education, and as a result, during the analysis of the reality of the implementation of inclusive education, they reached the values that show that the leading aspects are important and that it is necessary to prepare society and the educational environment for improving the quality of life. Moghadas et al (2022) after any disruptions in the work they have done and to move towards a sustainable future, the need to leap forward, the durability of recent urban initiatives and traditional top-down initiatives, the durability of effective strategies, plans and applicability in a time and place that is less likely to lead to the concept of the durability of the converter is intended to open the way to deal with. As a result of technology and a review of the literature on the durability of the converter, they found that a comprehensive understanding of the complexities and capabilities of using technology for transformative endurance was lacking, and they came to the conclusion that this field would be useful.…”
Section: Related Studiesmentioning
confidence: 99%